2023
DOI: 10.1523/jneurosci.1365-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sodium- and Chloride-Sensitive Sites in the Slack Channel

Abstract: The Slack channel (KCNT1, Slo2.2) is a sodium and chloride-activated potassium channel that regulates heart rate and maintains the normal excitability of the nervous system. Despite intense interest in the sodium gating mechanism, a comprehensive investigation to identify the sodium-sensitive and chloride-sensitive sites has been missing. In the present study, we identified two potential sodium-binding sites in the C-terminal domain of the rat Slack channel by conducting electrophysical recordings and systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Whilst aspartate and isoleucine at position 884 could be closely accommodated in the surrounding pocket, together with the smaller alanine and valine sidechains with some leeway, substituting the larger glutamate and phenylalanine sidechains resulted in steric clashes with T922 (Figure 5). D884 was mutated to asparagine in rat K Na 1.1 by Xu and others (21), resulting in Na + -insensitivity, and we found that this mutation also resulted in a steric clash in silico (not shown).…”
Section: Resultssupporting
confidence: 50%
See 4 more Smart Citations
“…Whilst aspartate and isoleucine at position 884 could be closely accommodated in the surrounding pocket, together with the smaller alanine and valine sidechains with some leeway, substituting the larger glutamate and phenylalanine sidechains resulted in steric clashes with T922 (Figure 5). D884 was mutated to asparagine in rat K Na 1.1 by Xu and others (21), resulting in Na + -insensitivity, and we found that this mutation also resulted in a steric clash in silico (not shown).…”
Section: Resultssupporting
confidence: 50%
“…This acidic pocket together with D884 were recently proposed by both Xu and others (21) and Zhang and others (22) to be a potential cation binding site. Mutating the equivalent of D884 in rat K Na 1.1 to asparagine rendered the channel non-functional at intracellular Na + concentrations to up to 2 M (21). Consequently, and supported by molecular dynamics simulations, this aspartate was proposed as one of two Na + -binding sites in each subunit.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations